Monitoring and Evaluating Projects : A Step-by-Step Primer on Monitoring, Benchmarking, and Impact Evaluation - Grun, Rebekka E. (World Bank, Washington, DC, 2013)
This paper attempts to be a practical step-by-step guide to prepare and carry out benchmarking and impact analyses of projects. It's purpose is to attempt to present analytical tools solidly grounded in economic theory all while focusing on the practical questions of evaluations. Little space is given to theory, in order to spend more time on the actual steps involved, trying to make this paper as easy-to-use as possible. The paper is divided in two parts: the first part gives a rationale for quantitative evaluations and provides detailed operative guidance for benchmarking and impact evaluation (Chapter 1-4); and the second part provides templates for the tools needed in an evaluation, such as a data collection checklist, a focus group guide, and an example Terms of Reference (TOR) to subcontract an impact evaluation (Chapter 5).